The Correlation between Wearing High Heels and Pain Intensity on Calcaneus Area and Range of Motion Ankle Changes - Muhamad Hasan; Indah Amin Sugiharti; Dwita Aryadina Rachmawati (Journal of Agromedicine and Medical Sciences, 2020)
High heeled shoes or commonly called high heels, is a type of shoe with high sole designed. Wearing high heels can make women more beautiful and attractive. But, the use of high heels are not appropriate with public’s knowledge about how to wear these shoes properly and correctly. It is proved by so many musculosceletal injuy cases because of wearing high heels. Injury cases that mostly appear is pain on calcaneus area as a result of plantar fasciitis and achilles tendinitis. Besides causing injury, the use of high heels also can cause the range of motion ankle become changed due to body postural adaptation during wearing high heels. The aim of this study is to determine the correlation between wearing high heels and pain Intensity on calcaneus area and range of motion ankle changes. This is an analytical survey study with cross sectional study design. This study using women workers in Matahari Departement Store Johar Plaza Jember and Roxy Square Jember who met inclusion and exclusion criteria. Pain intensity on calcaneus area was measured with visual analog scale (VAS) questionnaire and the large of range of motion ankle was measured with goniometer. Spearman correlation test result between wearing high heels and pain intensity on posterior and medial calcaneus area is p<0,05, this result indicates that there is significant correlation between wearing high heels and pain intensity on posterior and medial calcaneus area. While correlation between wearing high heels and range of motion ankle changes has result>0,05, this result indicates that there is no significant correlation between wearing high heels and range of motion ankle canges. Keywords: High heels, pain intensity on calcaneus area, range of motion ankle changes